Synthetic application of chalcogenonium salts: beyond sulfonium. Issue 2 (12th December 2022) - Bastidas Ángel, Alix Y.; Campos, Philipe Raphael O.; Alberto, Eduardo E.
Abstract : Selenonium and telluronium salts are useful reagents in organic transformations. Their application and comparisons with sulfonium analogues are presented herein. Abstract : The application of chalcogenonium salts in organic synthesis has grown enormously in the past decades since the discovery of the methyltransferase enzyme cofactor S -adenosyl-l -methionine (SAM), featuring a sulfonium center as the reactive functional group. Chalcogenonium salts can be employed as alkylating agents, sources of ylides and carbon-centered radicals, partners for metal-catalyzed cross-coupling reactions and organocatalysts. Herein, we will focus the discussion on heavier chalcogenonium salts (selenonium and telluronium), presenting their utility in synthetic organic transformations and, whenever possible, drawing comparisons in terms of reactivity and selectivity with the respective sulfonium analogues.